Exploring business model innovation in response to exogenous crises – a multiple case study of small and medium sized manufacturers in KwaZulu Natal, South Africa - Sewnandan, Sandeepa (University of Pretoria, 2024)
Dissertation (MBA)--University of Pretoria, 2023